Functional characterisation of alpha(1)-adrenoceptors in denervated rat vas deferens - Campos, M.; Morais, P. D.; Pupo, A. S. (Springer, 2003)
We investigated whether or not surgical denervation of the rat vas deferens changes the alpha(1)-adrenoceptor subtypes involved in the contractions to noradrenaline. Denervated vas deferens was approximate to22 times more sensitive to noradrenaline (pD(2)=7.35 +/- 0.04) than control vas (pD(2)= 6.01 +/- 0.03). This difference in noradrenaline potency was eliminated when cocaine (6 muM) was added to control vas (pD(2)=7.22 +/- 0.04). The noradrenaline-induced contractions of control and denervated vas deferens were insensitive to the alpha(1B)/alpha(1D)-adrenoceptor alkylating agent chloroethylclonidine (100 muM, 45 min). The concentration-response curves to noradrenaline in control and denervated vas deferens were competitively antagonised by prazosin (pA(2)approximate to9.6), WB-4101 (pA(2)approximate to9.5), 5-methyl urapidil (pA(2)approximate to8.4), phentolamine (pA(2)approximate to8.7), yohimbine (pA(2)approximate to6.9), BMY 7378 (pA(2)approximate to6.9) and indoramin (pA(2)approximate to8.7). After the treatment of control and denervated vas deferens with phenoxybenzamine, the partial agonist oxymetazoline antagonised competitively the concentration-response curves to noradrenaline showing pA(2) values approximate to7.4 in both groups. We conclude that noradrenaline-induced contractions in control and denervated rat vas deferens are mediated by alpha(1A)-adrenoceptors and that surgical denervation of the rat vas deferens is not able to change the alpha(1)-adrenoceptor subtypes involved in the contractions to noradrenaline.
Keywords: rat vas deferens; denervation; alpha(1A)-adrenoceptors